I want to prove the binary resolution proof that if I have $a \vee b$ and $ \lnot b \vee c$ then this will imply $$ a \vee c$$
Now I want to do it this way $$(a \vee b) \wedge ( \lnot b \vee c) \implies (a \vee c)$$
So i want to distribute this and among the expression to arrive at the conclusion.
I tried to apply the distribute property and hence I have $$(a \wedge (\lnot b \vee c) \vee (b \wedge ( \lnot b \vee c))$$
and then I will have $$((a \wedge \lnot b) \vee (a \wedge c)) \vee (b \vee \lnot b) \vee (b \wedge c)) $$
I know that $$b \wedge \lnot b$$ will cancel but then How would I simplify
$$((a \wedge \lnot b) \vee (a \wedge c)) \vee (b \wedge c)) $$
? any suggestions please ! ?
We have to prove that :
is a tautology.
After your application of distributivity, we have :
We can rewrite it as :
that is equivalent to :
By distributivity again, we get a conjunction of three disjuncts :
Thus, the original formula is equivalent to :
i.e. it is a tautology, and thus we can conclude (again) that the Resolution rule is sound.